Adverse reactions after COVID-19 vaccination: an integrative review (Research, Society and Development, 2022)
Objective: To identify in the literature the main adverse reactions of vaccines against COVID-19. Methodology: Integrative review, conducted using the Virtual Health Library (VHL), Scopus (Elsevier) and Embase search strategies. Through the following research question: “What adverse reactions have been evidenced in the literature in patients vaccinated by COVID-19?”. RAYYAN software was used to import the data. Results: 1,816 studies were identified, of which 57 included the review. The results were summarized in the form of a table and there were several reactions classified into local, systemic and severe reactions, there was a higher incidence of adverse reactions in females and the manifestations were immediate to late. Conclusion: It was evidenced that the majority of post-vaccination adverse reactions by COVID-19 were local, immediate and self-limiting. Nurses should promote actions to prevent and identify post-vaccination adverse reactions.